“Corporate Financial Crimes” in T.Bennett, F.Brookman, M.Maguire & H.Pierpoint (eds) Handbook on Crime, - John Minkes (Willan, 2010)
This chapter reviews the literature on corporate financial crimes, discussing case examples, theoretical understandings and potential responses.